Development of the online interactive software “Push Me-Pull Me” - Coates, Lawrence; McLeod, Iain; Broadbent, Oliver; Yiatros, Stylianos (My University, 2012)
The project aim was to develop the online interactive software for qualitative structural analysis “Push mePull me” (PmPm) in www.expeditionworkshed. org, a website dedicated to civil and structural engineering students that is created and maintained by Expedition Engineering’s educational arm ThinkUp. Specifically, guidelines for the use of PmPm within the Workshed were developed to enable its use as a free tool in higher education institution virtual learning environments, including tutorial exercises in worksheets purposely created to engage students and enhance their intuitive understanding of structural behaviour. Finally, the use of PmPm in parallel with formal lectures was promoted through visits and workshops.
Keywords: Qualitative structural analysis; Online educational tools; Engineering education